Traits Selection in Created Personal Ads and Sociosexuality: A New Method to Assess Sexual Strategy in Humans - Kajstura, Justyna; Pawłowski, Bogusław (Anthropological Review, 2025)
Sociosexuality (SO) refers to preferring sexual interactions with or without commitment. Those who prefer long-term relationships have restricted SO, and those who pursue short-term relationships have an unrestricted SO. Sociosexuality may be assessed by Sociosexual Orientation Inventory (SOI-R). Here, we test a new method to assess SO. Respondents are asked to create a personal ad by selecting six out of 10 suggested preferred traits in a partner. Among these 10 traits, there were two traits in each of five evolutionary relevant categories i.e., attractiveness, commitment, resources, cognitive and social skills. We hypothesize that seeking attractiveness/sensuality in a potential partner is related to concentrating on mating investments (higher SOI-R) and to commitment to parental investment (lower SOI-R). Out of 416 subjects who participated in the study, 299 (188 women) were included in the analysis. We found that choosing two traits of attractiveness is related to a less restricted SO, while preference for two commitment traits category characterizes those with a more restrictive SO. No relationship between SOI-R and the preference for cognitive skills or resources was found. Women with more and men with less restricted SO sought partners with better social skills. The proposed new method could be used to assess reproductive strategy.